The 3-in-1 Policy Model for Strengthening Urban Food Security: An Integrated Approach - Muhammad Fikri Alan; M. Ijaz Alfan Maulami; Mohammad Hazyar Arumbinang (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Kediri City has experienced a significant increase in agricultural land conversion. This issue remains a severe problem in agrarian development locally and nationally. Continuous eviction and conversion of agricultural land will reduce the country's food production capacity and hinder the achievement of food security. Previous research identifies farmer poverty as the main driver of agricultural land conversion. This study proposes an integrative 3 in 1 policy to prevent further conversion, encompassing farmer empowerment, land extensification reorganization, and regulatory reform. All three elements will be integrated into one sustainable agricultural policy. This research employs empirical legal methods with a sociological approach, collecting qualitative data from farmers in Kediri City and comparing it with existing theories, laws, and regulations. The findings indicate that farmers have not yet received optimal empowerment. Farmers tend to convert land because farming no longer ensures prosperity. High fertilizer prices, expensive labour costs, and uncertain harvest prices are various inhibiting factors. Thus, the 3 in 1 Policy could be an alternative to solve this problem. Kota Kediri mengalami peningkatan alih fungsi lahan pertanian yang begitu masif. Alih fungsi lahan pertanian masih menjadi persoalan yang sangat serius dalam pengembangan pertanian, baik lokal maupun nasional. Apabila setiap jumlah tanah pertanian yang ada itu terus menerus digusur dan dialihfungsikan, maka kemampuan negara untuk memproduksi pangan tentu juga akan terus menurun. Ketahanan pangan juga akan semakin sulit untuk tercapai. Dari penelitian terdahulu yang dilakukan, kemiskinan petani menjadi penyebab utama terjadinya alih fungsi lahan pertanian. Penelitian ini akan merekomendasikan gagasan tentang bagaimana alih fungsi lahan pertanian itu tidak terus menerus terjadi. Gagasan ini berwujud kebijakan integratif 3 in 1 policy. Gagasan ini meliputi aspek pemberdayaan petani, pengaturan ulang tentang ekstensifikasi, serta perubahan regulasi alih fungsi. Ketiganya akan berwujud dalam satu kebijakan pertanian yang berkelanjutan. Penelitian ini adalah penelitian yuridis empiris, dengan metode pendekatan sosiologis. Hasil penelitian menunjukkan, petani masih merasa belum mendapatkan pemberdayaan yang optimal. Petani cenderung mengalihfungsikan tanah, karena bertani tidak lagi mendatangkan kesejahteraan. Berbagai faktor penghambat yang terjadi adalah mahalnya harga pupuk, biaya pekerja yang makin mahal, serta harga hasil panen yang tidak menentu. Maka, gagasan 3 in 1 Policy bisa menjadi salah satu alternatif untuk menyelesaikan persoalan ini.